Indirect additive manufacturing technique in rapid vacuum casting - Mohd Mustafa, Nur Nabilah; Ma’aram, Azanizawati; Sudin, Izman; Wahab, Md Saidin (Penerbit UTM Press, 2020)
In the early stage of product development process, concept development, initial design and preliminary product testing are conducted in terms of aesthetic and functionality values. Prototypes play an important role to accelerate new product development to the market especially in the early stage. Presently, Additive Manufacturing (AM) has successfully plays a significant role in producing functional products in many industries including automobile, biomedical, aerospace and telecommunication. Indirectly, AM can also be used to produce tools, inserts or mold and dies to assist the Traditional Manufacturing (TM) processes such as milling, turning or casting. The common term used is Rapid Tooling. AM has the ability to produce parts with design flexibility in shorter time. However, one of the drawbacks is there will be no cost reduction with an increasing of production volume. ..